Penilaian Standar Mutu Pada Sistem Perpustakaan Sekolah Di MTs Muhammadiyah 8 Ujungpangkah Menggunakan Standar ISO 20000 Dengan Analisis Fishbone Diagram - Desiyarotur Risykiyana; Muhammad Yusril Bahtiar; Farid Sukmana (Puslitbang Sekawan Institute Nusa Tenggara, 2021)
In the development of a system, quality assurance is needed. A system can be said to be of good quality if it meets the needs of the user. Quality can be measured from various points of view. One point of view to measure software quality is to focus on service management systems. To determine the quality of a system, it is necessary to analyze the quality of the system. The school library system at MTs Muhammadiyah 8 Ujungpangkah has implemented a lot of service management systems to support the process of activities in the library. However, it is not yet known whether the system is in accordance with the assessment standards or not.The author uses the ISO 20000 standard to assess the requirements for obtaining a certificate in the library application by conducting various analyses. This study aims to analyze the application of the library system with ISO 20000. The analytical research methods used include determining clauses, checklists, Likert scale, maturity levels, and fishbone diagrams. The references that I take are based on the results of the analysis of the writing team that I have made including graphs, diagrams, clause scores, checklist scores, Likert scales, maturity levels, and fishbone diagrams. Based on the results of the author's analysis, the school library application system at MTs Muhammadiyah 8 Ujungpangkah does not meet the ISO 20000 standard so that there is still much that needs to be improved in the library system. The Likert scale score is only 11%, while to meet the ISO 20000 standard the Likert scale score must reach at least 60%. The overall problem with this analytical assessment that results in the Library System application not passing the ISO 20000 quality standard is the lack of a Likert scale score and fishbone diagram. With fishbone diagram, the main root cause is found with organitation structure that is not clear to monitor the application working. The hypothesis in this study can be the basis for future research so that the application can meet the feasibility test of the ISO 20000 quality standard.